Development and Study of the Properties of Impact-Resistant Ceramic Nanocomposite Coatings for Silicon; Glass and Ceramics; Vol. 77, iss. 3-4 - Bozhko I. A. Irina Aleksandrovna; Kalashnikov M. P. Mark Petrovich; Fedorishcheva M. V. Marina Vladimirovna; Khristenko Yu. F. Yury Fedorovich; Sergeev V. P. Viktor Petrovich (2020, 2020)
Title screen